Dimensi Kreativitas Dan Pengembangan Usaha Mikro Kecil Dan Menengah (UMKM) - Andi Hendrawan; Ferri Kuswantoro; Hari Sucahyawati (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2019)
Creativity is an important part of human life, and everyone is not freed from it. Creativity is one of supporting the existence of one's life. Everyone has creativity, and the difference is the level of creativity between people with each other. Research aims to prove the influence of the dimension of creativity to the development of SMEs. The population of research is MSMEs in Kamulyan Village, Bantarsari District, Cilacap Regency, amounting to 30 MSMEs, the sample uses saturated sample that is using whole population to be sample. (P = 0.01), there is no effect Dimension of process creativity to the development of MSMEs (P = 0.068), there is influence Dimension of product creativity to the development of MSMEs (P = 0,00) there is influence Dimension of press creativity to MSMEs development (P = 0,00).